Health service improvement using positive patient feedback: Systematic scoping review. - Rebecca Lloyd; James Munro; Kerry Evans; Amy Gaskin-Williams; Ada Hui; Mark Pearson; Mike Slade; Yasuhiro Kotera; Giskin Day; Joanne Loughlin-Ridley; Clare Enston; Stefan Rennick-Egglestone (PLoS ONE)
Background Healthcare services regularly receive patient feedback, most of which is positive. Empirical studies suggest that health services can use positive feedback to create patient benefit. Our aim was to map all available empirical evidence for how positive patient feedback creates change in healthcare settings. Methods Empirical studies in English were systematically identified through database searches (ACM Digital Library, AMED, ASSIA, CINAHL, MEDLINE and PsycINFO), forwards and backwards citation, and expert consultation. We summarise the characteristics of included studies and the feedback they consider, present a thematic synthesis of qualitative findings, and provide narrative summaries of quantitative findings. Results 68 papers were included, describing research conducted across six continents, with qualitative (n = 51), quantitative (n = 10), and mixed (n = 7) methods. Only two studies were interventional. The most common settings were hospitals (n = 27) and community healthcare (n = 19). The most common recipients were nurses (n = 29). Most outcomes described were desirable. These were categorised as (a) short-term emotional change for healthcare workers (including feeling motivated and improved psychological wellbeing); (b) work-home interactional change for healthcare workers (such as improved home-life relationships); (c) work-related change for healthcare workers (such as improved performance and staff retention). Some undesirable outcomes were described, including envy when not receiving positive feedback. The impact of feedback may be moderated by characteristics of particular healthcare roles, such as night shift workers having less interaction time with patients. Some factors moderating the change created by feedback are modifiable. Conclusion Further interventional research is required to assess the effectiveness and cost-effectiveness of receiving positive feedback in creating specific forms of change such as increases in staff retention. Healthcare managers may wish to use positive feedback more regularly, and to address barriers to staff receiving feedback.